Lightweight Cryptography for Security and Privacy Second International Workshop, LightSec 2013, Gebze, Turkey, May 6-7, 2013, Revised Selected Papers - Avoine, Gildas; Kara, Orhun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the proceedings of the 2th International Workshop on Lightweight Cryptography for Security and Privacy, LightSec 2013, held in Gebze, Turkey, during May 6-7, 2013. The 10 full papers presented together with 3 invited talks were carefully reviewed and selected from 27 submissions. The papers are grouped in topical sections on efficient Implementations and designs, block cipher cryptanalysis, wireless sensor networks, and cryptographic protocols.
Efficient Implementations and designs -- A Lightweight ATmega-based Application-Specific Instruction-Set Processor for Elliptic Curve Cryptography -- ITUbee: A Software Oriented Lightweight Block Cipher -- Block Cipher Cryptanalysis -- Related-Key Slide Attacks on Block Ciphers with Secret Components -- Differential Fault Attack on the PRINCE Block Cipher -- Multidimensional Meet-in-the-Middle Attacks on Reduced-Round TWINE-128 -- Wireless Sensor Networks -- An Implementation of the Hash-Chain Signature Scheme for Wireless Sensor Networks -- An adaptive security architecture for location privacy sensitive sensor network applications -- Cryptographic Protocols -- Secure & Lightweight Distance-Bounding -- Cryptanalysis and Improvement of a Provably Secure RFID Ownership Transfer Protocol -- An Efficient and Private RFID Authentication Protocol Supporting Ownership Transfer.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer Science; Data Encryption; Systems and Data Security; Computer Communication Networks